Analisis Desain Fasilitas Umum Bagi Penyandang Disabilitas (Sebuah Analisis Psikologi Lingkungan) - Triana Rosalina Noor (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2017)
Persons with disabilities, they have physical limitations, so they will have little difficulty in adjusting. These obstacles are exacerbated by environmental situations and public facilities that are not conducive to growth, participation and activity in life. This study aims to analyze an environmental design and public facilities that accommodate people with disabilities in everyday life based on environmental psychology studies. In addition, some concept formulations related to the design and evaluation of environmental and public facilities are drawn up using the most appropriate approach in respecting, protecting and fulfilling the rights of persons with disabilities. Through qualitative descriptive analysis of the existing conditions of persons with disabilities, it is hoped that the majority of the environment and public facilities still not designed for persons with disabilities, especially transportation facilities, shopping areas, parking lots, markets, parks and so on. Therefore, stakeholders should consider the design of the environment that can be accessed by persons with disabilities